2011
DOI: 10.1080/18146627.2011.603241
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in attitudes toward science among Northern Sotho speaking learners in South Africa

Abstract: Research shows that although most studies have explored the relationship between attitude and achievement in science only a few have been undertaken to reveal the nature of the relationship between affective variables and process outcomes in science. This study seeks to examine sex differences in attitude toward science among Northern Sotho speaking learners in South Africa. A random sample of 793 respondents (365 boys and 428 girls) in Grade 12 whose ages ranged from 17 to 24 years was selected from 27 school… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
0
1
1
Order By: Relevance
“…This finding represented a significant move away from previous work that found a gender divide favouring males ahead of females (e.g. Cherian & Shumba 2011;Flipsen & van der Weide 2009;McGregor & Bazi 2001;Ong & Lai 2006).…”
Section: Discussion Implications Contributions and Limitationscontrasting
confidence: 69%
See 1 more Smart Citation
“…This finding represented a significant move away from previous work that found a gender divide favouring males ahead of females (e.g. Cherian & Shumba 2011;Flipsen & van der Weide 2009;McGregor & Bazi 2001;Ong & Lai 2006).…”
Section: Discussion Implications Contributions and Limitationscontrasting
confidence: 69%
“…There appears to be a general consensus of the existence of a gender divide that favours males. In a study by Cherian and Shumba (2011) it was found that males show more positive attitudes towards science than females. Flipsen and van der Weide (2009) suggest that women have fewer options and opportunities to engage in new technologies largely because of their social position.…”
Section: Theoretical Backgroundmentioning
confidence: 99%